Gender differences in the effect of a 0.11% breath alcohol concentration on forward and backward gait - Gimunová, Marta; Bozděch, Michal; Novák, Jan; Vojtíšek, Tomáš (Scientific reports, 2022)
Alcohol contributes to a large number of diseases and health conditions related to injuries. The aim of our study was to evaluate gender differences in forward and backward gait when sober and at a breath alcohol concentration (BrAC) of 0.11%. Fifty females and fifty males participated in our study. The gait analysis was performed twice, when sober and after drinking a given amount of vodka mixed with orange juice. Under both conditions, participants were asked to walk forward and then backward on a Zebris platform. Multivariate analysis and the Mann-Whitney U test were used to compare the differences between genders when walking forward and backward. The Wilcoxon Signed Ranks test was used to compare the differences between 0.00% BrAC and 0.11% BrAC. Spearman's Rho was used to analyze the relationship between the AUDIT score, anthropometrical characteristics and the subjective score of drunkenness and gait parameters. The results show different strategies to improve stability during gait in women and men when intoxicated with alcohol. When intoxicated, males in forward gait increase their stability by increasing their foot rotation, while females increase their step width. A decrease in balance-related variables was observed in females when walking backward with a BrAC of 0.11%. Additionally, females tended to perform an increase in balance-related gait variables when subjectively feeling more drunk in both forward and backward gait. Different strategies to maintain stability during gait were observed in women and men. The results of our study show that alcohol intoxication has a greater impact on gait in females who tended to perform an increase in balance-related variables with an increase in their subjective score of drunkenness.
Keywords: Breath Tests; sexuální faktory; Ethanol; chůze; otrava alkoholem; Male; Alcoholic Intoxication; Gait; lidé; chůze (způsob); mužské pohlaví; ženské pohlaví; Female; Walking; Humans; dechové testy; ethanol; Sex Factors